1971
DOI: 10.1128/am.22.6.1030-1033.1971
|View full text |Cite
|
Sign up to set email alerts
|

Heat Resistance of Spores of Marine and Terrestrial Strains of Clostridium botulinum Type C

Abstract: Resistance to heat of spores of marine and terrestrial strains of Clostridium botulinum type C in 0.067 m phosphate buffer ( p H 7.0) was determined. The marine strains were 6812, 6813, 6814, and 6816; the terrestrial strains were 468 and 571. The inoculum level equaled 10 6 spores/tube with 10 replicate tubes for each time-temperature variable. Heating times were run at three or more temperatures to permit survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…In line with previous knowledge, spores of each C. botulinum group displayed different levels of heat resistance, with Group I spores being the most heat resistant, Group II being the least heat resistant [ 22 ], and Group III showing moderate heat resistance [ 50 ]. The observed D-values, however, were mostly lower than those previously reported, which is likely due to the spore purification used.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In line with previous knowledge, spores of each C. botulinum group displayed different levels of heat resistance, with Group I spores being the most heat resistant, Group II being the least heat resistant [ 22 ], and Group III showing moderate heat resistance [ 50 ]. The observed D-values, however, were mostly lower than those previously reported, which is likely due to the spore purification used.…”
Section: Discussionsupporting
confidence: 82%
“…While the heat resistance of Groups I and II C. botulinum spores has been widely studied for food safety purposes, studies on the heat resistance of Group III spores unrelated to human disease are scarce. An early study demonstrated different heat resistance patterns for Group III spores of terrestrial and marine origin, with terrestrial spores showing higher heat resistance than marine spores [ 50 ]. Both of our Group III strains could be characterized as terrestrial and showed resistance patterns similar to [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to C. botulinum groups I and II, which have long been recognized as the main causes of foodborne botulism, there is very little information defining the principles of control of C. botulinum type III strains. For thermal treatments under moist heat conditions commonly applied in food processing, the decimal D reduction times at 104°C of spores of group III strains ( n = 4) have been estimated to be 0.1–0.9 min ( Segner and Schmidt, 1971 ) and about 12 min ( Portinha et al, 2022 ) at 90°C ( n = 2). These sparse data suggest a resistance to moist heat much higher than that of spores of non-proteolytic C. botulinum group II, but also a much lower resistance than that of spores of proteolytic C. botulinum group I.…”
Section: Botulism and Animalsmentioning
confidence: 99%